La réforme des sociétés mutuelles d’assurance contre l’incendie dans la province de Québec - Bouchard, Jean-Marie (Assurances, 1986)
In the past, a large number of small mutual insurance companies existed in Quebec. Servicing the rural community, these mutuals were necessarily of local interest. But then, the need to strengthen them was felt and the movement had to be reorganized. With the passing of a new law (Chapter 17) assented to 20th June 1985, mutuals were grouped into a federation. The founding of a reinsurance company capable of sustaining the movement's development represented the final stage in the implementing of this organization, thus providing it with the tools necessary for growth. It is from this perspective that the author examines the new status of mutual insurance in Quebec.